Geographical mobility and qualification - a historical perspective - Oltmer, Jochen [Verfasser] (My University, 2013)
"The fundamental economic transformation of the past few decades has caused seismic shifts in the interrelationship between geographical mobility and qualification, the conditions, forms and consequences of which are mapped out in this article. The great mass migrations of the 19th and 20th centuries were characterised by the movement of people with low qualifications to become a 'cheap' and 'willing' workforce for the extraction and exploitation of the natural resources specific to their destinations. Although it is a valid observa - tion that migration has commonly been associated with gaining qualifications, in that era knowledge transfer due to the movement of specialists was only ever marginal in scale by comparison to the mass migrations of unqualified workers. In view of the accelerated pace of structural economic change since the Second World War, however, and the increasing level of professionalisation and specialisation in the most diverse fields of work, the acquisition of qualifications has since become a considerably more significant factor." (Autorenreferat, BIBB-Doku)
Keywords: G 1.3.3.3 Mobilität; Strukturwandel; Internationale Wanderung; Mobilität; Qualifikation; Wissenstransfer; Historische Entwicklung